2017
DOI: 10.1097/md.0000000000008365
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of central lymph node metastasis of papillary thyroid carcinoma

Abstract: Due to the lack of an accurate preoperative diagnostic method of central lymph node metastasis (CLNM) of papillary thyroid cancer (PTC), the prophylaxis of central lymph node dissection remains controversial. The present study investigated the clinicopathological features of PTC patients and the risk factors of CLNM. The clinicopathological features of PTC patients with respect to sex, age, initial symptoms, observation, tumor diameter, multifocality, extrathyroidal invasion, and pathological data combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
8
31
1
Order By: Relevance
“…By comparing the baseline clinical characteristics between patients in the primary tumor size ≤1 cm group and primary tumor size 1 to 4 cm group (Table ), our study found that the primary tumor size 1 to 4 cm group tended to show higher incidence of ETE and LNM. This is partly in accordance with the result from a recent study indicating that tumor diameter is an independent risk factor of central lymph node metastasis (CLNM) . Thus, larger tumor diameter in size 1 to 4 cm group could contribute to the possibility of CLNM.…”
Section: Discussionsupporting
confidence: 91%
“…By comparing the baseline clinical characteristics between patients in the primary tumor size ≤1 cm group and primary tumor size 1 to 4 cm group (Table ), our study found that the primary tumor size 1 to 4 cm group tended to show higher incidence of ETE and LNM. This is partly in accordance with the result from a recent study indicating that tumor diameter is an independent risk factor of central lymph node metastasis (CLNM) . Thus, larger tumor diameter in size 1 to 4 cm group could contribute to the possibility of CLNM.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency and the range of LOH/MSI, presented in our study as OFAL, significantly increases with tumor progression (clinical stages T2–T3), which is in concordance with the multistage model of carcinogenesis. The size of the tumor at the time of diagnosis is another important prognostic factor in the course of thyroid cancer [ 50 , 51 ]. Our study revealed that the highest percentage of allele loss was correlated with the diameter of the primary tumor being ≥ 3 cm, with a significant difference in the OFAL frequency compared with tumors < 1 cm.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies had limitations such as postoperatively assessable factor analysis (e.g., pathologic tumor size or lymphovascular invasion), enrolled patients with a high risk of CLNM (e.g., patients with a primary tumor size of > 10 mm), or heterogeneous enrolled patients, including both clinically CLNM positive and negative. [20][21][22] According to these limitations, in this study, we enrolled PTMC patients with negative CLNM on preoperative physical examination, US, and PET/CT and analyzed only preoperatively assessable factors. We found that a SUVmax of the primary tumor of > 3 was an independent preoperatively assessable factor predictive of pathologic CLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a larger tumor size have a higher risk of CLNM in PTC. 20 Furthermore, several studies have reported that tumor size is associated with CLNM even in cN0 PTMC. 22 Park et al and Wang et al exhibited that the tumor sizes > 7 mm and > 5 mm are significant predictive factors for CLNM in patients with cN0 PTMC.…”
Section: Discussionmentioning
confidence: 99%